2017
DOI: 10.3354/meps12083
|View full text |Cite
|
Sign up to set email alerts
|

Within-pair similarity in migration route and female winter foraging effort predict pair breeding performance in a monogamous seabird

Abstract: In long-lived monogamous animals, pair bond strength and durability are usually associated with higher fitness. However, whether pairs maximise fitness during the non-breeding season by maintaining contact during the winter or, instead, prioritise individual condition is unclear. Using geolocators recording spatial (light) and behavioural (immersion) data, we tracked pairs of the long-term monogamous Atlantic puffin Fratercula arctica during the non-breeding season to determine whether and how migratory strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The foraging behaviour during the non‐breeding season also differed between sexes. To our knowledge, only one study reported different at‐sea foraging activity between sexes in a migratory seabird species (Fayet, Shoji, Freeman, Perrins, & Guilford, ). We found that females tended to have higher foraging activity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The foraging behaviour during the non‐breeding season also differed between sexes. To our knowledge, only one study reported different at‐sea foraging activity between sexes in a migratory seabird species (Fayet, Shoji, Freeman, Perrins, & Guilford, ). We found that females tended to have higher foraging activity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures all trajectories start at the same point [0, 0] and standardized trajectories will be invariant to scaling and shifting (see Giao and Ahn 2016). We did not standardize coordinates when calculating NND in order to mirror the approach used in the previous ecological studies that used this measure (Fayet et al 2016(Fayet et al , 2017Shoji et al 2016;Votier et al 2017). When calculating LCSS and DTW we set δ to unlimited.…”
Section: Simulation Study Of Different Similarity Measuresmentioning
confidence: 99%
“…For example, most trajectory similarity studies in ecology use nearest neighbour distance (NND) (e.g. Freeman et al 2010;Demšar et al 2015;Fayet et al 2017;Votier et al 2017), but use of other trajectory similarity measures is rare. Moreover, in a recent review of metrics for ecological movement data (Seidel et al 2018) none of the similarity measures described here was mentioned yet they are routinely used in other fields.…”
Section: Introductionmentioning
confidence: 99%
“…, Fayet et al . ). In sedentary species, it would be relatively easy to coordinate pair activities from the onset of breeding, as mates can stay together in their local home‐ranges during the non‐breeding period (e.g.…”
mentioning
confidence: 97%
“…In long-lived monogamous bird species, pairs can maintain their bond for several years, which is important for successful breeding (Pyle et al 2001, S anchez-Macouzet et al 2014. During the breeding season, coordinated activities between mates contribute to the maintenance of pair bonds and thus probably enhance breeding success (Davis 1988, Spoon et al 2006, Mariette & Griffith 2012, S anchez-Macouzet et al 2014, Fayet et al 2017. In sedentary species, it would be relatively easy to coordinate pair activities from the onset of breeding, as mates can stay together in their local home-ranges during the non-breeding period (e.g.…”
mentioning
confidence: 99%